The N1–N2–LPC Pattern in Processing Advertising Pictorial Metaphors: An ERP Study - Cao, Shuo; Wang, Yanzhang; Chen, Hongjun; Wang, Huili (Frontiers in Psychology, 2018)
We investigated what the temporal processing is of advertising pictorial metaphors. After presenting “a word of product” and “its advertising pictures”, the experiment instructed participants to make a follow-up true-false judgement considering what the picture intended to suggest. A repeated-measures ANOVAs for a 2 (picture type: metaphor, non- metaphor) X 2 (prime-target condition: congruent, incongruent) X 3 (electrode site: Fz，Cz，Pz) experimental conditions was conducted on three components, N1 (100ms~150ms), N2 (200-300ms) and LPC (400-600ms and 600-1000ms).The results show that metaphor pictures elicited larger amplitude in N1 (broadly distributed), N2 (frontally biased) and LPC (parietally biased), roughly reflecting an entire process with an initial response to visual onsets, an early recognition of semantic violations and a prolonged reanalysis process of semantic integration. We argue that, different than verbal metaphors, this faster processing occurred due to the involvement of visual pathway. Keywords: pictorial metaphor; ERP; N1; N2; LPC